The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5144/0256-4947.2013.339
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequality in the clinical outcomes of equally treated acute coronary syndrome patients in Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVESGender associations with acute coronary syndrome (ACS), remain inconsistent. Gender-specific data in the Saudi Project for Assessment of Coronary Events registry, launched in December 2005 and currently with 17 participating hospitals, were explored.DESIGN AND SETTINGSA prospective multicenter study of patient with ACS in secondary and tertiary care centers in Saudi Arabia were included in this analysis.PATIENTS AND METHODSPatients enrolled from December 2005 until December 2007 includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
6
17
0
Order By: Relevance
“…22 Likewise, Birkemeyer et al reported that women were significantly older, with a higher prevalence of HTN and DM, and men were more likely to be current smokers. 23 Also, consistent with some other reports, 24,25 this study found no significant differences in treatment with primary PCI for women and men; however, DTB and STB were delayed slightly in women compared to men. These results support the findings of previous studies that women typically experienced a delay in DTB and STB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…22 Likewise, Birkemeyer et al reported that women were significantly older, with a higher prevalence of HTN and DM, and men were more likely to be current smokers. 23 Also, consistent with some other reports, 24,25 this study found no significant differences in treatment with primary PCI for women and men; however, DTB and STB were delayed slightly in women compared to men. These results support the findings of previous studies that women typically experienced a delay in DTB and STB.…”
Section: Discussionsupporting
confidence: 91%
“…20 Also, Hersi and colleagues' survey in Saudi Arabia showed that female gender was an independent risk factor for in-hospital mortality in STEMI. 24 Likewise, in a study conducted by Lawesson et al, female sex was independently linked to higher in-hospital mortality. 34 Differences in inclusion criteria and patients' selection, sample size, clinical and socio-demographic characteristics, and treatment strategies might unfold these different results.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Hersi A et al (2013) found in a study conducted in coronary syndrome patients, that males were predominant (77%). [33] In the current study, the percentage of Vitamin D deficiency individuals among the study population amounted to 46% and Vitamin D insufficiency 33%. Similarly, Luis et al (2013) confirmed high vitamin D deficiency among coronary syndrome patients (98%).…”
Section: Discussionmentioning
confidence: 93%
“…This finding was different from reports from South Africa (Ranjith et al, 2005). Males constituted more than half of patients admitted with ACS (56%), while reports from Saudi Arabia showed male predominance of 77% (Hersi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%